2018
DOI: 10.1186/s12889-018-5487-5
|View full text |Cite
|
Sign up to set email alerts
|

Active aging – resilience and external support as modifiers of the disablement outcome: AGNES cohort study protocol

Abstract: BackgroundPopulation aging increases the need for knowledge on positive aspects of aging, and contributions of older people to their own wellbeing and that of others. We defined active aging as an individual’s striving for elements of wellbeing with activities as per their goals, abilities and opportunities. This study examines associations of health, health behaviors, health literacy and functional abilities, environmental and social support with active aging and wellbeing. We will develop and validate assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 102 publications
0
99
0
3
Order By: Relevance
“…The scale has established validity and reliability in older adults. [4,37] In the current study, Cronbach's alpha was .88.…”
Section: Measures 231 Resiliencementioning
confidence: 48%
See 3 more Smart Citations
“…The scale has established validity and reliability in older adults. [4,37] In the current study, Cronbach's alpha was .88.…”
Section: Measures 231 Resiliencementioning
confidence: 48%
“…[1] Increasing life expectancy is often associated with particularly distressing adversities. [2][3][4] For instance, aging is accompanied by frailty with decline in physical and cognitive functioning, and an increase in multiple chronic diseases. [5,6] In addition, older adults experience psychological stress resulting from loss and bereavement, [7] decline in socioeconomic status with retirement, disability, [8] as well as concomitant loss of autonomy and depression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Finland, the University of Jyväslyöä has developed an instrument to measure active aging, called University of Jyväskylä Active Aging Scale (UJACAS). The tool consists of seventeen items focusing on activities and the capacity to maintain daily living [17]. In Thailand, a study used items including 17 selected indicators (range 0-1) to measure the active aging level and found that it is not high (average female = 0.64, male = 0.61) [18].…”
Section: Introductionmentioning
confidence: 99%